High-resolution insights into binding of unfolded polypeptides by the PPIase chaperone SlpA - Löw, Christian (2013)
SlpA is a 2-domain protein consisting of an FK506-binding protein (FKBP) domain that harbors the peptidyl-prolyl cis/trans-isomerase (PPIase) active site and a small insert-in-flap (IF) domain that endows the protein with chaperone activity. We have determined the structure of SlpA from Escherichia coli at 1.35-Å resolution. The overall structure is similar to other known structures of the FKBP-IF subfamily. However, by serendipity, the linker region of the purification tag binds in the chaperone binding groove of the IF domain, making this the first structure of an FKBP-IF protein in complex with a mimic of an unfolded chaperone substrate. The linker binds by β-sheet augmentation, thus completing the incomplete β barrel of the IF domain and shielding a considerable hydrophobic surface area from the solvent. Interestingly, a proline residue in trans configuration appears to be specifically recognized in a small pocket within the binding groove. Hence, the IF domain can preselect and prealign substrates with proline residues, which may explain how it enhances the catalytic efficiency and modulates the specificity of the FKBP domain in addition to its chaperone function. Based on pulldown results, we suggest that SlpA is likely to be involved in ribosome assembly.—Quistgaard, E. M., Nordlund, P., Löw, C. High-resolution insights into binding of unfolded polypeptides by the PPIase chaperone SlpA.